1960
DOI: 10.1113/jphysiol.1960.sp006496
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stimulation of extrinsic nerves on peristalsis and on the release of 5‐hydroxytryptamine in the large intestine of the guinea‐pig and of the rabbit

Abstract: Since the classical work by Trendelenburg (1917), many studies have been published on the peristaltic activity of the small intestine (for references see Builbring & Lin, 1958). In a recent investigation Biilbring & Lin (1958) found that small amounts of 5-hydroxytryptamine (5-HT) were continuously released into the lumen of an isolated loop of ileum and that 5-HT, if applied intraluminally, stimulated peristalsis by its action on sensory receptors deeply seated in the intestinal mucosa. These findings have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
25
1

Year Published

1961
1961
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 8 publications
6
25
1
Order By: Relevance
“…There is some evidence that this may be via an effect on a 2 -adrenoceptors (Mizutani et al 1990). Studies of the responses of the guinea-pig small intestine to sustained liquid distensions also indicate that MN stimulation inhibits propulsive contractions of the circular muscle (Lee, 1960;Kreulen et al 1983). This idea is supported by a recent study of the distal colon, which concluded that sympathetic nerves inhibit interneurons that carry reflex activity along the intestine (Spencer et al 1999a).…”
supporting
confidence: 65%
“…There is some evidence that this may be via an effect on a 2 -adrenoceptors (Mizutani et al 1990). Studies of the responses of the guinea-pig small intestine to sustained liquid distensions also indicate that MN stimulation inhibits propulsive contractions of the circular muscle (Lee, 1960;Kreulen et al 1983). This idea is supported by a recent study of the distal colon, which concluded that sympathetic nerves inhibit interneurons that carry reflex activity along the intestine (Spencer et al 1999a).…”
supporting
confidence: 65%
“…8), indicating that they are propulsive. Interestingly, although these contractions were found to be dependent on enteric neural circuits [as they were TTX-sensitive (29)], to our surprise fast nicotinic transmission was not required, since hexamethonium did not inhibit them nor their change their speed of propagation (27,29). Also, mecamylamine (100 M) failed to block the antegrade or retrograde peristaltic contractions, suggesting that the nicotinic transmission is unlikely to be involved in these peristaltic contractions.…”
Section: Neurogenic Peristalsis (Antegrade) and Antiperistalsis (Retrmentioning
confidence: 87%
“…In the colon, propulsive activity was investigated in situ by Bayliss & Starling (1900), Elliott & Barclay-Smith (1904), Raiford & Mulinos (1934a, b), Auer & Krueger (1947), Bozler (1949b), Hukuhara & Miyake (1959) and in the isolated organ by Langley & Magnus (1905), Tyrode (1910), Currie & Henderson (1926), Lembeck (1958), Lee (1960), Hulkuhara, Nakayama & Nanba (1961), Hukuhara & Neya (1968), and MacKenna & McKirdy (1969).…”
Section: Introductionmentioning
confidence: 99%